Islamic landmarks of Aden between the seventh and tenth centuries AH - Rabda, Ahmed Saleh (Al-Adab Journal, 2015)
This research through a light on old religious and educational institutions such as mosques, schools, leagues, and others in Aden, and their role in the cultural and social life in the specified period. *Quoting specimens of these old mosques, schools and Islamic leagues.*Highlighting the role of these religious and educational institutions in the graduation of high level scientific cadres and their role in the cultural and social life etc.*Development of intellectual, cultural and scientific movement in these schools and their reaction in the society .*Appearance of efficient judges and scholars in these schools who wrote scientific books which enriched the Yemeni library at that time, and formed a part of the educational curricula.*These graduates , including judges and jurists, in view of their high characters and high level sincerity, education and fear of conscience, participated in taking up administrative and financial responsibilities in Aden and other places.*These institutions were interested in traditional and intellectual sciences in particular, like astronomy, algebra, request, comparison and music. They became specialized colleges.*Close ethnical correlation among all religious and educational institutions in the whole Yemeni homeland.*Influences of Aden school on Hadhrmaaut school, as an example.*The juristic books which were compiled by jurists of these schools to deal with subjects with particular significance, for example “ Appendix on classes of Alshafiyah for Al asnawi, by the scholar Abdulla Ben Ahmed Bamakhramah, which dealt with subjects related to Portugese piracy in the southern coasts, particularly Aden and Hadhramaut. *In this period Aden had become a scientific center. It did not engage only in trade, but also in culture and education.* A large number of scholars came from inside and outside to study in its schools , and to settle, and trade in its markets. Aden had become at that time a prosperous trading market and trading port which received ships from all parts of the world.*Regulations were applied and complied with by judges, jurists, scholars, teachers, and regulation and law breakers were brought to account, and seized, jailed and tortured.*The graduates of these institutions participated in social life. For example they took up responsibility for tax trusts, ports, and repelled invaders and all forms of corrupts. . Objectives of the Research:1-Identify Aden religious and educational landmarks such as mosques, schools, leagues, corners, and khanqats and others if any.2-To refer to the sources exclusively for finding out the history of ancient religious and educational institutions which still keep their old names, such as Aden Jama, Aaban, Al aidroos, Alyaqootiah etc.3- To refer to comparisons, conclusions, and locations on which these institutions were constructed with the purpose of reaching proportional facts about their historical locations.4-To keep whatever remain of these institutions despite various constructions and amendments made to them.5- To find out the impacts of these institutions on the cultural and social life in Aden. 6- To carry out excavations to find out these locations and search for their roots in the Yemeni soil. Approach of the Research:We relied on the historical approach in the study of the old and wiped out accomplishments.Analyzed the historical sources which are within our access and subject them, as possibly as we can , to examination, investigation and tes.Studied biographies of scholars , particularly those who visited Aden in order to know more about the news of these religious and educational institutions . Familiarize ourselves, as much as possible, with reports of early scholars, researchers, travelers, archeologists who visited the landmarks and historical sites of AdenTo know about the preliminary sources of the antiquities, historical sites, and visit the places of these historical sites, and look intently at the photographs and drawings which had been taken at early time or now, and compare them with the outstanding antiquities, and witnesses who watched some of these civilizations in the middle of the last century.Hold comparison between them and other antiquities in other regions , or know the reasons for their disappearance here while their identical survived in other locations of the Yemeni homeland. For example by looking at the pattern of building Alyaqootiah in Heis, gives us a comprehensive idea about the type of building Aden Yaqootiah, and similarly Mansooriah Guban. Most like they are still surviving . There is a good picture for it in Almansooriah in Aden, and so on.Location of the Research: The research is limited to religious and educational landmarks and historical sites in ancient Aden city, particularly, the landmarks and historical sites which were mentioned in their current names in the sources without references.Time Borders of the Research:With the occurrence of some historical turning points which might deviate the study from its historical context in narrow limits, by virtue of various incidents the time borders of this research stand between the second century until the tenth century Higri, the eighth and the sixteenth century A.D.We focused on religious and educational institutions which were mentioned in the sources. The list before us today is totally in need of other intensive efforts to be made to know their origins , roots and names which were subjected to many and various changes which obliterated totally their old names and constructional origins.